Children's perception on gaming technology / Khairiyah Salleh - Salleh, Khairiyah (2013)
Though today's children have many chances to interact with IT technology, what they understand about technology from their point of view still needs to be explored. In this research, the researcher is reporting on how children define IT technology and what they understand about technology to be in a real-life context. Besides, the researcher also studied on the gaming experiences and their emotional responses towards gaming. Hence these studies also looking at the perception on gaming technologies preferred by children. The researcher used qualitative research aiming to identify the differences in children's definitions and their practical understanding of technology. The participatory approach is being selected in order to get to know with the children of Generation Z. The purpose of this study is to find out children's perspectives on gaming technology. The study will explore more on their experiences while playing games and their emotional responses towards games. Furthermore, the researcher wants to explore in depth children's imagination in what are really the kinds of features of gaming technology needed that is suitable for children to have. The findings will be useful to the technology and gaming developers in making their decision in developing the gaming devices that are usable and yet it is coming with the fun experiences for children and young peoples.